STRATEGI PENGEMBANGAN USAHA DISTILASI MINYAK ATSIRI DAUN CENGKEH DI PT. TJANDI SEWU BARU : Business Development Strategy For Clove Leaf Essential Oil Distillation At Pt. Tjandi Sewu Baru - Muhammad Diki Adiyanto (Program Studi Agribisnis Faperta Universitas Muhammadiyah Bengkulu, 2026)
The findings reveal that the company’s primary strengths include a strategic business location close to raw material sources, abundant natural resources (clove leaves), consistent growth in production, high-quality clove oil, and adequate transportation access. Conversely, the weaknesses identified are limited promotional activities, reliance on traditional technology, and lengthy distillation processes. From the external perspective, the opportunities consist of high clove leaf oil prices, a relatively wide marketing network, strong consumer confidence in product quality, and sustained demand for clove leaf oil. However, the company also faces threats such as natural disasters, fluctuating commodity prices of clove leaf essential oil, and the emergence of new competitors. The evaluation results show that the total internal factor score is 3.17 and the external factor score is 3.25, positioning the company strategically strong for sustainable business development. The alternative strategies formulated include: (1) enhancing production capacity by optimizing the strategic location and availability of raw materials to meet growing market demand, (2) creating added value through product diversification, (3) maintaining and improving product quality to sustain high selling prices and consumer trust, and (4) establishing partnerships with distributors to expand marketing networks by leveraging adequate transportation access.